Managerial Leadership Styles in Problem-Solving Conferences - Delbecq, André L. (Academy of Management Journal, 1964)
The article presents an overview of a study which focused on effective managerial leadership in conference groups which were held within a bureaucratic organization and dealt with a decision-task necessitating judgmental and heuristic problem-solving. The author summarizes the prior theory and research underlying the hypotheses which provide the fulcrum around which this study was organized. The conclusions of prior research are presented in propositional form, followed by a citation of types of studies supporting the propositions.